Multinational Firms and Job Tasks - Katariina Nilsson Hakkala; Fredrik Heyman; Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2008)
We use Swedish matched employer-employee data to analyze the impact of multinational activity and foreign acquisitions on the relative demand for different job tasks. We contribute to the literature by using a conceptualization from the recent literature in international economics and define the division of labor in terms of job tasks. Our econometric results show that multinational firms, both foreign and domestic, are associated with higher shares of non-routine tasks and tasks requiring personal interaction than local firms. Moreover, acquisitions of local firms by both foreign and domestic MNEs tend to increase the relative demand for non-routine and interactive job tasks, i.e. tasks that are not easily offshored. As a comparison, dividing labor according to educational attainment does not capture the found effects on relative labor demand.
Keywords: F16; F21; F23; J23; 330; FDI; Cross-Border Acquisitions; Multinational Enterprises; Foreign Ownership; Job Tasks; Labor Demand; Skill Groups; Multinationales Unternehmen; Arbeitsnachfrage; Anforderungsprofil